Why a Logbook? A backpack journey as a metaphor for product design education - Clemente, Violeta
Recent literature suggests that the development of cognitive skills should constitute explicit learning objectives in design education. The work describes an educational intervention designed with the intention of promoting the creative and critical thinking performance of a group of Portuguese design students. To this end, creativity and critical thinking tests, pre and post intervention, were applied to the experimental group and to a control group. The intervention was based on two fundamental theoretical assumptions: (1) students’ thinking skills can be promoted by the introduction of Design Thinking as a learning content, and (2) this work should be complemented by the promotion of students’ metacognitive reflection. Comparing the learning process, by analogy, with a backpack journey, a Logbook concept as an educational tool to potentially promote students’ self-reflection was developed. Compared with the control group, results indicate a positive evolution of creative thinking skills in the experimental group.